Performance of Polycaprolactone/Hydroxyapatite (PCL/HA) Composite Blended by Ultrasound Assisted Melt Blending / Suffiyana Akhbar ... [et al.] - Akhbar, Suffiyana; Subuki, Istikamah; Sharudin, Rahida Wati; Ismail, Muhammad Hussain (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Conventional melt blending is limited in producing of biocomposite material implants with high loading of hydroxyapatite (HA) content for orthopaedic application and bone tissue engineering. The objective of this study is to produce polycaprolactone/hydroxyapatite (PCL/HA) composite blend with high loading of HA by assist conventional melt blending with ultrasonic wave. Rheological behaviour, morphology, thermal behaviour and chemical characteristics of PCL/HA composite blends were investigated. This study found that 400 Watt of ultrasonic wave provided sufficient process ability of PCL/HA composite blend up to 30 wt% of HA based on rheological behaviour. Meanwhile field emission scanning electron microscopy (FESEM) micrograph showed that the size of as-received HA was reduced during extrusion and better dispersion of HA was obtained although some agglomerates of HA were observed. Melting temperature and crystallization temperature of PCL/HA composite blends were almost similar and did not change significantly regardless to HA content. However, crystallinity of PCL/HA composite blends were increased as HA content increased from 10 to 30 wt%.